Oral Steroids Should Be Avoided in Patients with RA and ILD - Freeman, Sara (MD Conference Express, 2014)
Long-term use of oral glucocorticosteroids should be avoided in patients with rheumatoid arthritis (RA) who have concomitant interstitial lung disease (ILD), according to the findings of a British initiative.